The Role Of Visum Et Repertum As A Provision Effort On Criminal Financing - Lilik Eko Sukaryono; Amin Purnawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
In the process of investigating criminal cases of persecution relating to the body, health, and human lives, it requires the assistance of a medical expert. The assistance of a doctor with his medical science of justice as stated in the Visum et repertum which he made is absolutely necessary. The formulation of the problem that was formed in this study is how the role of visum et repertum as evidence in the implementation of court cases of persecution in the Blora State Court, and what obstacles and solutions that occur in the form of evidence visum et repertum in cases of criminal abuse. Juridical sociology as an approach method used in this study with research specifications with descriptive methods. The data used consisted of primary data and secondary data using interview and literature study methods. Based on the research it was concluded (1) The role of Visum et repertum in the case of mistreatment in case decision number 184 / Pid.B / 2018 / PN Bla, the judge weighed on the elements in Article 351 paragraph 1 of the Criminal Code in which the result was a feeling of discomfort, pain or injury, which is based on evidence in the form of Visum et repertum on the victim's body. (2)Obstacles in proving in the form of visum et repertum in cases of torture include the qualification of wounds based on the legal needs confusing a doctor, standardization of the determination of the degree of injury to be poured on the Visum et repertum, Provisions for the signing of the post visum et repertum letter by the doctor, Request for visum et repertum which is lacking / incomplete, Visum Request Letter arrives late. Keywords: Visum Et Repertum; Evidence; Criminal Acts Of Persecution.